Flexible laminated perovskite solar cell and preparation method thereof

By introducing polymer elastomers into the wide-bandgap perovskite absorber layer of flexible laminate perovskite solar cells, the problem of flexible cells being prone to fracture and interface falling off under mechanical stress is solved, and higher bending resistance and photoelectric conversion efficiency are achieved.

CN119546041APending Publication Date: 2025-02-28NANJING UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411713610.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Flexible laminate perovskite solar cells are prone to electrode fracture and interface fallout under mechanical stresses such as bending and folding, which affects their long-term use and performance stability.

Method used

In the preparation process of the wide-bandgap perovskite light absorbing layer, polymer elastomer is introduced, and prepared by spin coating or coating method, the waterproofing performance and mechanical strength of the light absorbing layer are enhanced, the thickness of the tunnel composite layer is thinned, and the bending resistance of the device is improved.

Benefits of technology

By introducing polymer elastomers, the water barrier performance and mechanical strength of the wide-bandgap perovskite absorber layer are improved, the bending resistance and long-term stability of the flexible stacked perovskite solar cells are enhanced, and the photoelectric conversion efficiency and device service life are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119546041A_ABST
    Figure CN119546041A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible laminated perovskite solar cell and a preparation method of the flexible laminated perovskite solar cell. The solar cell sequentially comprises a flexible substrate, a bottom electrode, a carrier transport layer 1, a wide-band-gap perovskite light absorption layer, a carrier transport layer 2, a tunneling composite layer, a carrier transport layer 3, a narrow-band-gap perovskite light absorption layer, a carrier transport layer 4 and a top electrode from a light receiving front side to a light receiving back side. Wherein the wide-band-gap perovskite light absorption layer is made of a wide-band-gap perovskite material and a polymer elastomer. According to the invention, the polymer elastomer is introduced in the preparation process of the wide-band-gap perovskite light absorption layer, so that the waterproof performance of the wide-band-gap perovskite light absorption layer is enhanced, the thickness of the subsequent tunneling composite layer is reduced, and the bending resistance of the solar cell device is improved; and meanwhile, the problem that the wide-band-gap top cell is dissolved when the narrow-band-gap perovskite light absorption layer is prepared subsequently is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solar cells, and in particular relates to a flexible laminated perovskite solar cell and a preparation method thereof. Background Art

[0002] As one of the important renewable energy technologies, the development of solar cells has received widespread attention. Although crystalline silicon solar cells are the mainstream in the market, their efficiency improvement has approached their theoretical limit efficiency of 29.43%. The main bottleneck is that single-junction cells are difficult to fully utilize the solar spectrum, resulting in energy loss. In addition, the production and processing costs of silicon materials are high, which limits the further improvement of their cost-effectiveness. Against this background, perovskite cells have been developed and emerged due to their unique optoelectronic properties. Perovskite materials have adjustable band gaps, high absorption coefficients, and excellent carrier transport properties, and their preparation process is simple and the cost is low, which makes their efficiency rapidly improve in a short period of time, becoming a new focus in the field of solar cells.

[0003] In order to further improve the conversion efficiency of solar cells, researchers have begun to focus on the development of tandem solar cells. By combining sub-cells with different band gaps, tandem cells can absorb the solar spectrum more effectively and reduce energy loss, thus breaking through the efficiency bottleneck of single-junction cells. The theoretical limit efficiency of two-junction tandem cells is as high as 43%. Perovskite materials have excellent photoelectric properties and adjustable band gaps, making them an ideal choice for the preparation of high-efficiency tandem cells. Among them, flexible tandem perovskite solar cells can be applied to wearable devices, portable electronic devices, awnings, vehicle roofs, smart building skins, drones, etc. due to their high efficiency, low cost, bendability, and lightness, to achieve power supply anytime, anywhere, and improve energy utilization efficiency and product intelligence. Therefore, the research and development of flexible tandem perovskite solar cells has become an important development direction for solar cells in the future.

[0004] However, there are still many technical difficulties in the research and development of flexible laminated perovskite solar cells. Compared with rigid laminated perovskite solar cells, flexible batteries are prone to problems such as electrode breakage and interface detachment under mechanical stress such as bending and folding, which affects the long-term use of the battery. Therefore, it is necessary to improve the durability of the battery under repeated bending and stretching conditions by introducing bending-resistant materials or improving interface contact. Furthermore, the thickness of the tunneling composite layer connecting the upper and lower sub-batteries will also affect the flexibility of the battery. Usually, the tunneling composite layer of a flexible laminated perovskite solar cell needs to have two functions: composite carriers and barrier solvents. However, an overly thick tunneling composite layer will reduce the bending performance of the battery due to its own brittleness, affecting its durability in flexible applications, while an overly thin tunneling composite layer will result in poor solvent barrier properties. The narrow-bandgap perovskite film preparation process may dissolve the wide-bandgap perovskite film portion, affecting the performance and stability of the device. In addition, when preparing wide-bandgap perovskite films on flexible substrates, holes are easily generated on their surfaces, leading to an increase in defects, accelerating the recombination rate of carriers, and reducing the lifetime of carriers, thereby affecting the performance of flexible laminated perovskite solar cells.

[0005] Therefore, it is very important to design a method to enhance the mechanical durability of flexible stacked perovskite solar cells and improve the photoelectric conversion efficiency and working stability of flexible cells. Summary of the invention

[0006] One of the purposes of the present invention is to provide a flexible laminated perovskite solar cell, which comprises, from the light-receiving front side to the light-receiving back side, a flexible substrate, a bottom electrode, a carrier transport layer 1, a wide bandgap perovskite light-absorbing layer, a carrier transport layer 2, a tunneling composite layer, a carrier transport layer 3, a narrow bandgap perovskite light-absorbing layer, a carrier transport layer 4 and a top electrode;

[0007] The wide band gap perovskite light absorbing layer is made of a wide band gap perovskite material and a polymer elastomer.

[0008] Furthermore, the wide bandgap perovskite light absorbing layer is made in one of the following ways:

[0009] Method 1: When preparing a wide bandgap perovskite light-absorbing layer by spin coating, a polymer elastomer is added to an antisolvent and then annealed;

[0010] Method 2: When a wide bandgap perovskite light-absorbing layer is prepared by a coating method, an anti-solvent containing a polymer elastomer is coated again before or after the wet film formed by the wide bandgap perovskite material is annealed, and then annealed again.

[0011] Furthermore, the polymer elastomer is selected from polyolefin elastomer (POE), polyisobutylene (PIB), thermoplastic polyurethane (TPU), styrene-ethylene / butylene-styrene (SEBS), and ethylene-vinyl acetate copolymer (EVA).

[0012] Furthermore, the anti-solvent is an anti-solvent commonly used in the art, such as anisole, toluene, chlorobenzene, dichlorobenzene, ethyl acetate, n-butanol, isopropanol, etc.

[0013] Furthermore, the wide bandgap perovskite material is an ABX3 type compound, wherein A is selected from the group consisting of formamidinium ions (FA + ), methylamine ion (MA + ), cesium ion (Cs + ); B is lead ion (Pb 2+ );X is selected from iodide ion (I - ), bromide ion (Br - ), chloride ion (Cl - ).

[0014] In the present invention, the flexible substrate, bottom electrode, carrier transport layer 1, carrier transport layer 2, tunneling composite layer, carrier transport layer 3, narrow bandgap perovskite light absorption layer, carrier transport layer 4 and top electrode can all be made of materials familiar to those skilled in the art.

[0015] The flexible substrate can be an organic polymer substrate, a metal foil or a flexible ultra-thin glass, wherein the organic polymer can be but not limited to polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyimide (PI), polydimethylsiloxane (PDMS), etc.; the metal foil can be but not limited to copper foil, silver foil, gold foil, aluminum foil, titanium foil, stainless steel foil, etc.

[0016] The bottom electrode and the top electrode can be made of transparent conductive oxides, metals, conductive organic matter or conductive carbon materials, wherein the transparent conductive oxide can be but not limited to indium tin oxide (ITO), indium zinc oxide (IZO), indium tungsten oxide (IWO), fluorine-doped tin oxide (FTO), aluminum-doped zinc oxide (AZO), etc.; the metal can be but not limited to a combination of one or more metal materials such as gold, silver, aluminum, copper, etc.; the conductive organic matter can be but not limited to highly conductive poly 3,4-ethylenedioxythiophene-polystyrene sulfonate (PEDOT-PSS), etc.; the conductive carbon material can be but not limited to a combination of one or more materials of carbon nanotubes, graphene and other carbon electrode materials.

[0017] The carrier transport layer 1 and the carrier transport layer 3 are made of p-type or n-type semiconductor materials with the same conductivity type. The p-type semiconductor material can be, but is not limited to, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), 2,2',7,7'-tetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-MeOTAD), poly-3,4-ethylenedioxythiophene-polystyrene sulfonate (PEDOT-PSS), [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz), [4-(9H-carbazole-9-yl)butyl]phosphonic acid (4PACz), [2-(3,6-dimethoxy-9H-carbazole-9-yl) [ethyl]phosphonic acid (MeO-2PACz), [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid (MeO-4PACz), (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid (Me-4PACz), nickel oxide (NiO), molybdenum oxide (MoO3), cuprous oxide (Cu2O) and the like; the n-type semiconductor material may be, but is not limited to, titanium oxide (TiO2), tin oxide (SnO2), zinc oxide (ZnO), vanadium oxide (V2O5), zinc tin oxide (Zn2SnO4), fullerene (C 60 ), graphene, fullerene derivative [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) and the like.

[0018] The carrier transport layer 2 and the carrier transport layer 4 are made of n-type or p-type semiconductor materials with opposite conductivity to the carrier transport layer 1. The n-type semiconductor material can be, but is not limited to, titanium oxide (TiO2), tin oxide (SnO2), zinc oxide (ZnO), vanadium oxide (V2O5), zinc tin oxide (Zn2SnO4), fullerene (C 60), graphene, fullerene derivative [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) and other one or more materials; p-type semiconductor materials can be but not limited to poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] (PTAA), 2,2',7,7'-tetrakis [N,N-di (4-methoxyphenyl) amino] -9,9'-spirobifluorene (Spiro-MeOTAD), poly 3,4-ethylenedioxythiophene-polystyrene sulfonate (PEDOT-PSS), [2- (9H-carbazole-9-yl) ethyl] phosphine A combination of one or more materials including [2PACz], [4-(9H-carbazole-9-yl)butyl]phosphonic acid (4PACz), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz), [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid (MeO-4PACz), (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid (Me-4PACz), nickel oxide (NiO), molybdenum oxide (MoO3), and cuprous oxide (Cu2O).

[0019] The tunneling composite layer can be a dense film made of transparent conductive oxide, or a combination of a dense transparent semiconductor layer and an ultra-thin metal layer / conductive nanoparticle layer. The transparent conductive oxide can be, but is not limited to, indium tin oxide (ITO), indium zinc oxide (IZO), indium tungsten oxide (IWO), fluorine-doped tin oxide (FTO), aluminum-doped zinc oxide (AZO), etc. The conductivity type of the transparent semiconductor layer must be consistent with the conductivity type of the carrier transport layer 2; wherein the n-type transparent semiconductor material can be, but is not limited to, a combination of one or more materials such as titanium oxide (TiO2), tin oxide (SnO2), zinc oxide (ZnO), vanadium oxide (V2O5), zinc tin oxide (Zn2SnO4), etc.; the p-type transparent semiconductor material can be, but is not limited to, a combination of one or more materials such as nickel oxide (NiO), molybdenum oxide (MoO3), cuprous oxide (Cu2O), etc. The material of the ultra-thin metal layer may be, but is not limited to, a combination of one or more materials such as gold, palladium, silver, titanium, chromium, nickel, aluminum, and copper; the material of the conductive nanoparticle layer may be, but is not limited to, a combination of one or more materials such as indium tin oxide (ITO), indium zinc oxide (IZO), indium tungsten oxide (IWO), fluorine-doped tin oxide (FTO), and aluminum-doped zinc oxide (AZO).

[0020] The narrow bandgap perovskite light absorbing layer is made of perovskite material ABX3, wherein A is selected from formamidinium ion (FA + ), methylamine ion (MA + ), cesium ion (Cs + ); B is selected from lead ions (Pb 2+ ), tin ions (Sn 2+), Germanium ions (Ge 2+ );X is selected from iodide ion (I - ), bromide ion (Br - ), chloride ion (Cl - ).

[0021] The second object of the present invention is to provide a method for preparing the above-mentioned flexible laminated perovskite solar cell, comprising the following steps:

[0022] A wide bandgap perovskite light absorbing layer is prepared on the carrier transport layer 1, and the wide bandgap perovskite light absorbing layer is prepared in one of the following ways:

[0023] Method 1: When preparing a wide bandgap perovskite light-absorbing layer by spin coating, a polymer elastomer is added to an antisolvent and then annealed;

[0024] Method 2: When a wide bandgap perovskite light-absorbing layer is prepared by a coating method, an anti-solvent containing a polymer elastomer is coated again before or after the wet film formed by the wide bandgap perovskite material is annealed, and then annealed again.

[0025] In the present invention, the flexible substrate, bottom electrode, carrier transport layer 1, carrier transport layer 2, tunneling composite layer, carrier transport layer 3, narrow bandgap perovskite light absorption layer, carrier transport layer 4 and top electrode can all be made by methods familiar to those skilled in the art, such as electron beam evaporation, thermal evaporation, magnetron sputtering, atomic layer deposition, spin coating, scraping and other deposition methods.

[0026] The present invention introduces a polymer elastomer during the preparation process of a wide bandgap perovskite light absorbing layer to enhance the water-proof performance of the wide bandgap perovskite light absorbing layer, reduce the thickness of the subsequent tunneling composite layer, improve the bending resistance of the solar cell device, and avoid the problem of the wide bandgap top cell being dissolved during the subsequent preparation of the narrow bandgap perovskite light absorbing layer. In addition, the introduction of the polymer elastomer can effectively reduce the holes on the surface of the wide bandgap perovskite light absorbing layer on the flexible substrate, reduce the defects of the perovskite, reduce the recombination rate of electrons and holes, increase the life of the carriers, and prepare a more compact perovskite film, thereby improving the performance of the flexible laminated perovskite solar cell.

[0027] In one embodiment of the present invention, the method is applied to 0.049 cm 2 In the preparation of flexible wide-bandgap perovskite solar cells with an effective area, the photoelectric conversion efficiency was increased from 16.80% to 18.21%; the optimized device still achieved 84.29% of the initial performance after 2000 bending cycles under a bending radius of 5 mm, while the unoptimized device could not work properly after 1600 bending cycles under the same conditions. 2In the preparation of flexible two-junction stacked perovskite solar cells with an effective area, the photoelectric conversion efficiency was increased from 24.82% to 26.34%; the optimized device still achieved an efficiency of 93.62% of the initial performance after 800 bending cycles under a bending radius of 12.5 mm, while the unoptimized device could not work normally after 800 bending cycles under the same conditions.

[0028] Compared with the prior art, the present invention has the following advantages in introducing a polymer elastomer into a wide bandgap perovskite light-absorbing layer when preparing a flexible laminated perovskite solar cell: 1) by enhancing the water-proof performance of the surface of the wide bandgap perovskite light-absorbing layer, the thickness of the subsequent tunneling composite layer is reduced, thereby improving the bending resistance of the solar cell device; 2) the introduction of the polymer elastomer can effectively improve the solvent barrier capacity of the transmission layer and the waterproof capacity of the perovskite layer, thereby avoiding the problem of the wide bandgap top cell being dissolved during the preparation of the subsequent narrow bandgap perovskite light-absorbing layer; 3) the introduction of the polymer elastomer can effectively reduce the holes on the surface of the wide bandgap perovskite light-absorbing layer on the flexible substrate, reduce the defects of the perovskite, reduce the recombination rate of electrons and holes, increase the lifetime of the carriers, and prepare a relatively dense perovskite film, thereby improving the performance of the flexible laminated perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Schematic diagram of the device structure of flexible stacked perovskite solar cells.

[0030] Figure 2 Contact angle measurements of wide bandgap perovskite films for control and optimized samples.

[0031] Figure 3 These are optical micrographs of the sheared portion of the wide-bandgap perovskite films of the control and optimized samples after the tunneling composite layer was grown.

[0032] Figure 4 Comparison of bending test results of flexible wide bandgap perovskite solar cells and flexible stacked perovskite solar cells, with bending radii of 5mm and 12.5mm respectively.

[0033] Figure 5 Scanning electron micrographs of the control and optimized samples.

[0034] Figure 6 Fluorescence spectra and time-resolved photoluminescence images of the control sample and optimized sample.

[0035] Figure 7 Current density-voltage curves of the control and optimized samples of flexible wide-bandgap perovskite solar cells and flexible stacked perovskite solar cells. DETAILED DESCRIPTION

[0036] The preferred embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that the following examples are provided only for the purpose of illustration and are not intended to limit the scope of the present invention. Those skilled in the art may make various modifications and substitutions to the present invention without departing from the purpose and spirit of the present invention.

[0037] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0038] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0039] Example 1

[0040] This example is a control sample flexible laminated perovskite solar cell, using Figure 1 The device structure shown in the figure has a specific preparation process as follows:

[0041] (1) PET / ITO was used as a flexible conductive substrate, where ITO was used as the bottom electrode of the battery. The flexible conductive substrate was scrubbed with deionized water mixed with ITO cleaning solution, and then ultrasonically cleaned in deionized water, acetone, and isopropanol for 15 min respectively, and then blown dry. The flexible conductive substrate was attached to a glass sheet of the same size with double-sided tape to facilitate the subsequent preparation of other functional layers. Finally, it was placed in a UV ozone cleaning machine for 15 min to remove the organic residues remaining on the surface of the substrate and increase the surface wettability.

[0042] (2) Taking NiO nanoparticles as an example, the carrier transport layer 1 was prepared. The NiO nanoparticles prepared in advance by a hydrothermal method were dispersed in an appropriate amount of deionized water at a concentration of 15 mg / mL (about 0.2 mmol / mL). After stirring evenly, the mixture was scraped onto the bottom electrode and then annealed in air at 100°C for 10 min to obtain a NiO film with a thickness of 20-30 nm.

[0043] (3) Using FA 0.8 Cs 0.2 PbI 1.95 Br 1.05 As the material of the wide bandgap perovskite light absorbing layer, FA was weighed in molar ratio in a glove box filled with an inert gas such as nitrogen or argon. 0.8 Cs 0.2 PbI 1.95 Br 1.05 The perovskite was prepared by dissolving the weighed drug in a mixed solution of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) at a volume ratio of 4:1 and stirring for 5 hours. In a glove box, a wide bandgap perovskite light-absorbing layer was prepared by a doctor blade method and annealed on a hot plate at 100°C for 15 minutes to obtain a crystallized wide bandgap perovskite light-absorbing layer.

[0044] (4) In a nitrogen glove box, a 20 nm thick C layer was evaporated on the prepared wide bandgap perovskite light absorption layer in a high vacuum environment by vacuum thermal evaporation. 60 As an electron transport layer (carrier transport layer 2).

[0045] (5) Using atomic layer deposition technology in C 60 A 50nm thick dense SnO2 layer is deposited on the surface as a solvent barrier layer in the tunneling composite layer, and then a 0.6nm thick ultra-thin Au film is deposited by vacuum thermal evaporation for composite carriers. The two are combined as a tunneling composite layer.

[0046] (6) The PEDOT-PSS solution was coated onto the tunneling composite layer by a solution method in air, annealed on a hot plate at 100° C. for 10 min to form a carrier transport layer 3 with a thickness of approximately 20 nm, and then the sample was transferred to a nitrogen glove box.

[0047] (7) Using FA 0.8 Cs 0.2 Pb 0.5 Sn 0.5 I3 is used as the material of the narrow bandgap perovskite light-absorbing layer. FA is weighed in a glove box filled with an inert gas such as nitrogen or argon at a molar ratio. 0.8 Cs 0.2 Pb 0.5 Sn 0.5 For the perovskite of I3, the weighed drug was dissolved in a mixed solution of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of DMF to DMSO of 8:1, and then 10% molar ratio of stannous fluoride was added and stirred for 10 hours. In a glove box, a narrow bandgap perovskite light-absorbing layer was prepared by a doctor blade method, and annealed on a hot plate at 100°C for 7 minutes to obtain a crystallized narrow bandgap perovskite light-absorbing layer.

[0048] (8) In a nitrogen glove box, a 20 nm thick C layer was sequentially evaporated on the prepared narrow bandgap perovskite light absorbing layer in a high vacuum environment by vacuum thermal evaporation. 60 A 7nm thick BCP (2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline) is used as the electron transport layer (carrier transport layer 4) of the device, and finally a 150nm copper layer is thermally evaporated as the top electrode to obtain a flexible laminated perovskite solar cell device.

[0049] The prepared flexible laminated perovskite solar cells were removed from the glass substrate in a nitrogen glove box for testing and packaging.

[0050] Example 2

[0051] This embodiment is an optimized flexible laminated perovskite solar cell. Figure 1 The device structure shown in the figure has a specific preparation process as follows:

[0052] (1) PET / ITO was used as a flexible conductive substrate, where ITO was used as the bottom electrode of the battery. The flexible conductive substrate was scrubbed with deionized water mixed with ITO cleaning solution, and then ultrasonically cleaned in deionized water, acetone, and isopropanol for 15 min respectively, and then blown dry. The flexible conductive substrate was attached to a glass sheet of the same size with double-sided tape to facilitate the subsequent preparation of other functional layers. Finally, it was placed in a UV ozone cleaning machine for 15 min to remove the organic residues remaining on the surface of the substrate and increase the surface wettability.

[0053] (2) Taking NiO nanoparticles as an example, the carrier transport layer 1 was prepared. The NiO nanoparticles prepared in advance by a hydrothermal method were dispersed in an appropriate amount of deionized water at a concentration of 15 mg / mL (about 0.2 mmol / mL). After stirring evenly, the mixture was scraped onto the bottom electrode and then annealed in air at 100°C for 10 min to obtain a NiO film with a thickness of 20-30 nm.

[0054] (3) Using FA 0.8 Cs 0.2 PbI 1.95 Br 1.05 As the material of the wide bandgap perovskite light absorbing layer, FA was weighed in molar ratio in a glove box filled with an inert gas such as nitrogen or argon. 0.8 Cs 0.2 PbI 1.95 Br 1.05 The perovskite was prepared by dissolving the weighed drug in a mixed solution of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) at a volume ratio of 4:1 and stirring for 5 hours. In a glove box, a wide bandgap perovskite light-absorbing layer was prepared by a doctor blade method, and then a 2 mg / mL POE anisole solution was doctored onto the unannealed wet film of the wide bandgap perovskite light-absorbing layer by a doctor blade method, and then annealed on a hot plate at 100°C for 15 minutes to obtain a crystallized wide bandgap perovskite light-absorbing layer.

[0055] (4) In a nitrogen glove box, a 20 nm thick C layer was evaporated on the prepared wide bandgap perovskite light absorption layer in a high vacuum environment by vacuum thermal evaporation. 60 As an electron transport layer (carrier transport layer 2).

[0056] (5) Using atomic layer deposition technology in C 60A 15 nm thick dense SnO2 layer is deposited on the surface as a solvent barrier layer in the tunneling composite layer, and then a 0.6 nm thick ultra-thin Au film is deposited by vacuum thermal evaporation for composite carriers. The two are combined as the tunneling composite layer.

[0057] (6) The PEDOT-PSS solution was coated onto the tunneling composite layer by a solution method in air, annealed on a hot plate at 100° C. for 10 min to form a carrier transport layer 3 with a thickness of approximately 20 nm, and then the sample was transferred to a nitrogen glove box.

[0058] (7) Using FA 0.8 Cs 0.2 Pb 0.5 Sn 0.5 I3 is used as the material of the narrow bandgap perovskite light-absorbing layer. FA is weighed in a glove box filled with an inert gas such as nitrogen or argon at a molar ratio. 0.8 Cs 0.2 Pb 0.5 Sn 0.5 For the perovskite of I3, the weighed drug was dissolved in a mixed solution of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of DMF to DMSO of 8:1, and then 10% molar ratio of stannous fluoride was added and stirred for 10 hours. In a glove box, a narrow bandgap perovskite light-absorbing layer was prepared by a doctor blade method, and annealed on a hot plate at 100°C for 7 minutes to obtain a crystallized narrow bandgap perovskite light-absorbing layer.

[0059] (8) In a nitrogen glove box, a 20 nm thick C layer was sequentially evaporated on the prepared narrow bandgap perovskite light absorbing layer in a high vacuum environment by vacuum thermal evaporation. 60 A 7nm thick BCP (2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline) is used as the electron transport layer (carrier transport layer 4) of the device, and finally a 150nm copper layer is thermally evaporated as the top electrode to obtain a flexible laminated perovskite solar cell device.

[0060] The prepared flexible laminated perovskite solar cells were removed from the glass substrate in a nitrogen glove box for testing and packaging.

[0061] Figure 2 The contact angle test of the wide bandgap perovskite film prepared by the control sample and the optimized sample is shown. Compared with the control sample, the optimized sample has a larger contact angle, which indicates that the wide bandgap perovskite film has stronger hydrophobicity after the introduction of POE.

[0062] Figure 3Optical micrographs of the wide bandgap perovskite films of the control and optimized samples at the shearing point after the tunneling composite layer was grown are shown. Obvious cracks can be seen at the shearing point of the control sample, while the cracks of the optimized sample are smaller and basically invisible, which indicates that the thinning of the tunneling composite layer after the introduction of POE can effectively improve the flexibility of the device.

[0063] Figure 4 The bending test results of flexible wide bandgap perovskite solar cells and flexible stacked perovskite solar cells were compared, with bending radii of 5mm and 12.5mm respectively. The optimized sample of the flexible wide bandgap perovskite solar cell can still achieve 84.29% of the initial performance after 2000 bending cycles under the bending condition of a curvature radius of 5mm, while the control sample cannot work normally after 1600 bending cycles under the same conditions; further, the optimized sample of the flexible stacked perovskite solar cell can still achieve 93.62% of the initial performance after 800 bending cycles under the bending condition of a curvature radius of 12.5mm, while the control sample cannot work normally after 800 bending cycles under the same conditions. This shows that the optimized sample after the introduction of POE can still maintain a high efficiency after the same number of bendings as the control sample, showing a higher level of anti-bending ability.

[0064] Figure 5 Scanning electron microscope images of the control sample and the optimized sample are shown. The formation of holes can be observed on the surface of the control sample, while the surface of the optimized sample is more uniform and dense, which shows that the introduction of POE can inhibit the formation of holes on the surface of wide-bandgap perovskite, effectively inhibit the precipitation of lead iodide, improve the interface characteristics, improve the stability of the battery, and enhance the photoelectric conversion efficiency.

[0065] Figure 6 The fluorescence spectra and time-resolved photoluminescence images of the control sample and the optimized sample are displayed, indicating that the introduction of POE can further reduce the defects of perovskite, reduce the recombination rate of electrons and holes, and increase the carrier lifetime.

[0066] Figure 7 The current density-voltage curves of the control and optimized samples of flexible wide bandgap perovskite solar cells and flexible stacked perovskite solar cells are shown. The optimized sample has a higher open circuit voltage (V OC ) and fill factor (FF), thereby improving the conversion efficiency of flexible perovskite solar cells; at 0.049cm 2 In the preparation of flexible wide-bandgap perovskite solar cells with an effective area, the photoelectric conversion efficiency was increased from 16.80% to 18.21%; at 0.049 cm 2 In the preparation of flexible two-junction stacked perovskite solar cells with an effective area, the photoelectric conversion efficiency was increased from 24.82% to 26.34%.

Claims

1. A flexible laminated perovskite solar cell, comprising, from the light-receiving front side to the light-receiving back side, A flexible substrate, a bottom electrode, a carrier transport layer 1, a wide bandgap perovskite light absorption layer, a carrier transport layer 2, a tunneling composite layer, a carrier transport layer 3, a narrow bandgap perovskite light absorption layer, a carrier transport layer 4 and a top electrode, characterized in that the wide bandgap perovskite light absorption layer is made of a wide bandgap perovskite material and a polymer elastomer.

2. The flexible laminated perovskite solar cell according to claim 1, characterized in that: The wide bandgap perovskite light absorbing layer is made by one of the following methods: Method 1: When preparing a wide bandgap perovskite light-absorbing layer by spin coating, a polymer elastomer is added to an antisolvent and then annealed; Method 2: When a wide bandgap perovskite light-absorbing layer is prepared by a coating method, an anti-solvent containing a polymer elastomer is coated again before or after the wet film formed by the wide bandgap perovskite material is annealed, and then annealed again.

3. The flexible laminated perovskite solar cell according to claim 2, characterized in that: The polymer elastomer is selected from polyolefin elastomer, polyisobutylene, thermoplastic polyurethane, styrene-ethylene / butylene-styrene, and ethylene-vinyl acetate copolymer.

4. The flexible laminated perovskite solar cell according to claim 3, characterized in that: The anti-solvent is selected from anisole, toluene, chlorobenzene, dichlorobenzene, ethyl acetate, n-butanol, and isopropanol.

5. The flexible laminated perovskite solar cell according to claim 1, characterized in that: The wide bandgap perovskite material is an ABX3 type compound, wherein A is selected from formamidinium ion, methylamine ion, and cesium ion; B is lead ion; and X is selected from iodine ion, bromide ion, and chloride ion.

6. The method for preparing the flexible laminated perovskite solar cell according to claim 1, characterized in that: The following steps are involved: A wide bandgap perovskite light absorbing layer is prepared on the carrier transport layer 1, and the wide bandgap perovskite light absorbing layer is prepared in one of the following ways: Method 1: When preparing a wide bandgap perovskite light-absorbing layer by spin coating, a polymer elastomer is added to an antisolvent and then annealed; Method 2: When a wide bandgap perovskite light-absorbing layer is prepared by a coating method, an anti-solvent containing a polymer elastomer is coated again before or after the wet film formed by the wide bandgap perovskite material is annealed, and then annealed again.

Citation Information

Patent Citations

  • Mechanically laminated perovskite solar cell and preparation method thereof

    CN105609640A

  • Perovskite two-end laminated solar cell and preparation method thereof

    CN112289933A

  • Double-sided light-receiving solar cell and preparation method and application thereof

    CN112670419A

  • Flexible perovskite solar cell and preparation method thereof

    CN114300618A

  • Perovskite / perovskite laminated cell

    CN117769271A